Evolution of competition in Vietnam industries over the recent economic transition - Tinh Doan; Philip Stevens (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
Vietnam has gone through massive economic restructuring from a socialist command economy to market-oriented economy. This provides an excellent example of a country that has experienced changes in competition regime. Economic reforms in late 1980s and 1990s and the introduction of pro-competitive policies in the first half of 2000s have radically altered the economic and, in particular, competitive environment. Understanding the evolution of competition across industries is an important step towards understanding the impact of economic reform on the economic performance of Vietnam as a result of the economic transition. In this paper, the authors investigate the evolution of competition in Vietnam during the economic transition using the price-cost margin (or Lerner Index) and the profit elasticity measure recently developed by Boone (Competition, 2000). This paper provides the first empirical study of intensity and evolution of competition across majority of industries in Vietnam in the last decade using firm-level data from the Vietnam Enterprise Census (VEC) conducted annually since 2000 by the Vietnam General Statistical Office (GSO).
Keywords: D40; L11; L5; P20; P30; 330; competition; industry; economic transition; Vietnam; Wettbewerb; Branchenentwicklung; Übergangswirtschaft; Vietnam